Acceptability and feasibility of inter-related activities to improve agency among African district health managers: A four-country study. Issue 7 (3rd July 2022) - Fonn, Sharon; Ray, Sunanda; Couper, Ian; Ezeh, Alex; Omigbodun, Akinyinka; Morhason-Bello, Imran; Ng'wena, Gideon; Oyungu, Eren; Muchiri, Lucy; Tumwine, James; Ibingira, Charles; Conco, Daphney; et al.
ABSTRACT: District health managers (DHMs) lead and manage Ministry of Health programmes and system performance. We report on the acceptability and feasibility of inter-related activities to increase the agency of DHMs in Kenya, Nigeria, South Africa and Uganda using a cross-sectional rapid appraisal with 372 DHMs employing structured questionnaires. We found differences and similarities between the countries, in particular, who becomes a DHM. The opportunity to provide leadership and effect change and being part of a team were reported as rewarding aspects of DHMs' work. Demotivating factors included limited resources, bureaucracy, staff shortages, lack of support from leadership and inadequate delegation of authority. District managers ranked the acceptability of the inter-related activities similarly despite differences between contexts. Activities highly ranked by DHMs were to employ someone to support primary care staff to compile and analyse district-level data; to undertake study tours to well-functioning districts; and joining an African Regional DHM Association. DHMs rated these activities as feasible to implement. This study confirms that DHMs are in support of a process to promote bottom-up, data-driven, context-specific actions that can promote self-actualisation, recognises the roles DHMs play, provides opportunities for peer learning and can potentially improve quality of care.